Ship-Iceberg Collision Database: background, operation, contributions & preliminary analysis - Caines, J. (National Research Council of Canada. Institute for Ocean Technology, 2004)
The Ship-Iceberg Collision Database is a collection of nearly six hundred and sixty ship and iceberg collisions in Northern waters. As the fourth consecutive engineering work term student to contribute to this project under the supervision of Brian Hill, Senior Technical Officer and Ice Tank Supervisor, NRC-IOT, this report outlines the contributions made to the project during the past work term, the methods of research utilized, and a preliminary analysis of the findings. It is intended that this project and report provide a means of forecasting the probability of collision with an iceberg in Northern waters, in an effort to engender safer ocean travel and stimulate further research and development regarding factors that affect the Safety of Life at Sea (SOLAS). Numerous research methods and sources were utilized in contributing to this project, primarily contemporary shipping registries, newspapers and gazettes. Trends and correlations discovered amongst incident parameters are examined using linear regression modeling, and prevalent findings are further discussed within the report. The preliminary analysis develops noted relationships between known incidents and collision parameters such as climatic conditions, vessel speed, and sea ice extent and iceberg sightings on the Grand Banks of Newfoundland. Historical fluctuations in sea ice extent, iceberg sightings and corresponding collisions are represented, providing insight into bygone disastrous eras. Though collisions now occur at a rate of approximately one to two incidents per year, the threat posed by ice has not diminished. Modern iceberg detection technologies such as radar, and the introduction of ice and iceberg monitoring agencies such as the International Ice Patrol, have been integral to the decrease of ship and iceberg collisions realized during the past century. Preventative measures must be furthered, and it is recommended that this project be maintained and marketed as a valuable online resource of ship and iceberg collision documentation and a ...